EFEK KOMITMEN ORGANISASI PADA TURNOVER INTENTION: STUDI KASUS PADA KARYAWAN INDUSTRI MANUFAKTURR JAWA BARAT - Pratiwi, Witri Aprilia (Journal of Business Management Education (JBME), 2020)
Turnover intention is still a major problem on a variety of companies, where this became important because with the onset of Turnover intention will affect the contribution to the organization. The high Turnover intention occurs on a variety of insustri, including the manufacturing industry. This study aimed to obtain (1) the level of organizational commitment, (2) the level of turnover intention, (3) the influence of organizational commitment on turnover intention. The unit of analysis in this study is the employees of the manufacturing industry Method of research this research uses kuantiatif. As well as the results of the research show that the influence of organizational commitment on turnover intention in the low category with the results to 26.11%, it is important to do because if the Turnover intention increases will have a negative impact for PT.X as, a result of poor performance, attendance increased, and will have an impact on job satisfaction, working conditions at the company.